المظاهرات السلمية تطبيقا لنظام الرقابة الشعبية في الفقه الإسلامي والقانون الوضعي الإندونيسي - Rusli Hasbi (Universitas Islam Negeri Jakarta, 2017)
Demonstration is one application model of the people supervision against the government’s performances, which is based on amr ma’ruf nahi munkar and aims to realize people’s aspirations when they want to change a law and a government policies or aims showed disagreement over what happens inside the country or a broad, such as injustice, etc, and Islam has legalized demonstration during carried out public interest and in order to maintain security and stability of society, the government also has ensured this demonstration with giving rights and freedoms to every citizen to express their aspirations in accordance with applicable laws. DOI: 10.15408/ajis.v17i1.6228